Post-treatments of polydopamine coatings influence cellular response - Davidsen, Maiken B.; Teixeira, Jorge Felipe Lima [UNESP]; Dehli, Jeppe; Karlsson, Christian; Kraft, David; Souza, Pedro P.C. [UNESP]; Foss, Morten (Elsevier, 2021)
Polydopamine (PDA) is the final oxidation product of dopamine or other catecholamines. Since the first reports of PDA coatings starting around 2007, these coatings have been widely studied as a versatile and inexpensive one-step coating option for biomaterial functionalization. The coating attach to a wide range of materials and can subsequently be modified with biomolecules or nanoparticles. However, as a strong candidate for biomaterial research and even clinical use, it is important to unravel the changes in physico-chemical properties and the cell-PDA interaction as a function of heat sterilization procedures and shelf storage periods. Four groups were examined in this study: titanium (Ti), PDA-coated Ti samples and PDA-coated Ti samples either stored for up to two weeks at room temperature or heated at 121 °C for 24 h, respectively. We used X-ray Photoelectron Spectroscopy (XPS), Time-of-Flight Secondary Ion Mass Spectrometry (ToF-SIMS) and Water contact angle (WCA) to characterize chemical composition and surface properties of the groups. Cell adhesion and proliferation was examined by three different cell types: human primary dermal fibroblasts (hDF), human epidermal keratinocytes (HaCaTs) and a murine preosteoblastic cell line (MC3T3-E1), respectively. Cells were cultured on PDA coated samples for 4 h, 3 days and 5 days. Both thermal treatment of PDA at 121℃ for 24 h and storage of the samples for 2 weeks increased the amount of quinone groups at the surface and decreased the amount of primary amine groups as detected by XPS and ToF-SIMS. Even though these surface reactions increased the WCA of the PDA coating, we found that the post-treatments increased cell proliferation for both hDFs, HaCaTs and MC3T3-E1 s as compared to pristine PDA. This emphasizes the importance of post-treatment and shelf-time for PDA coatings.
Keywords: Cell proliferation; Polydopamine; Post-treatment; Surface functionalization